2018
DOI: 10.1530/ec-18-0082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of Graves’ or non-Graves’ hyperthyroidism compared to TSH receptor antibody test

Abstract: BackgroundTSH receptor antibody (TRAb) is considered the gold standard diagnostic test for the autoimmunity of Graves’ disease (GD), which is commonly diagnosed clinically.AimTo evaluate the true positive (sensitivity) and true negative (specificity) rates of clinical diagnosis of GD or non-GD hyperthyroidism compared to the TRAb test.SettingUniversity teaching hospital in North West England.ParticipantsPatients in the Endocrinology service who had a TRAb measurement between December 2009 and October 2015.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Lauren Bell et al have found that the TRAb result was the definitive diagnosis against which we evaluated the sensitivity and specificity of clinical diagnosis [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lauren Bell et al have found that the TRAb result was the definitive diagnosis against which we evaluated the sensitivity and specificity of clinical diagnosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest clinicians utilize a positive TRAb measurement over their clinical judgement to confirm a diagnosis of GD. A TRAb measurement in the initial clinical assessment of all patients could potentially prevent an incorrect diagnosis being made in the first place [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RNASET2-FGFR1OP-CCR6 region at 6q27 and an intergenic region at 4p14 are two new susceptibility loci that had been found [20]. Moreover, thyroid-stimulating hormone receptor and major histocompatibility complex class II versions have strong associations with thyroid stimulating hormone receptor autoantibodies (TRAb)-positive GD [21]. Compared with healthy controls, GD patients have higher rate of peripheral blood mononuclear cell conversion into CD34 + fibrocytes.…”
Section: Pathophysiology Of Graves' Diseasementioning
confidence: 99%